Echocardiographic features of post−transcatheter aortic valve implantation thrombosis and endocarditis. Issue 3 (21st December 2017) - Spartera, Marco; Ancona, Francesco; Barletta, Marta; Rosa, Isabella; Stella, Stefano; Marini, Claudia; Italia, Leonardo; Montorfano, Matteo; Latib, Azeem; Alfieri, Ottavio; Margonato, Alberto; Colombo, Antonio; et al.
Abstract : Background: Transcatheter heart valve thrombosis (THV‐t) and endocarditis (THV‐e) are relevant complications after transcatheter aortic valve implantation (TAVI). Transcatheter heart valve (THV) dysfunction definition is mostly based on Doppler (stenosis/regurgitation) without considering leaflets characteristics. Purpose: To evaluate the additional diagnostic value of leaflets echocardiographic features over Doppler when prosthetic valve complication is suspected. Methods: Among 621 post‐TAVI patients, 128 cases with probable valve complication were identified. THV‐t was finally diagnosed in 13 patients (10%) and THV‐e in 8 (6%), while the remaining 107 (84%) had no definitive diagnosis of thrombosis/endocarditis (THV‐no). We analyzed at 2 time points (baseline and follow‐up) both traditional Doppler parameters and leaflets morpho‐functional features. Results: Both Doppler and leaflets parameters showed high sensitivity (sensitivity 92%) and low specificity (ranging from specificity 32% to 74%) in detecting THV‐t. Interestingly, the combination of mean aortic pressure gradient ≥20 mm Hg and leaflet thickening significantly improved the specificity of echocardiography for diagnosis of THV thrombosis (specificity 94%). On the other hand, echocardiographic diagnosis of THV endocarditis remained limited by very low sensitivity despite showing high specificity. Conclusions: The combination of Doppler and leaflets parameters can improve the echocardiographic diagnosis of THV thrombosis in post‐TAVI patients with suspicious symptoms, via a significant increase in the overall test specificity. This would potentially allow more rational gatekeeping to more expensive/invasive diagnostic examinations (eg, CT scan) or therapeutic trials (eg, unnecessary anticoagulation).